Law in public health practice - Goodman, Richard A. (Richard Alan), 1949-; Hoffman, Richard E. (New York ; Oxford : Oxford University Press, 2007)
Written jointly by experts in law and in public health, this book is designed specifically for public health practitioners, lawyers, healthcare providers, and law and public health educators and students. It identifies, defines, and clarifies the complex principles of law as they bear on the practice of public health.
Includes bibliographical references.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public health laws -- United States; Public health personnel -- Legal status, laws, etc. -- United States; Public health -- United States